2017
DOI: 10.1042/cs20160916
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of miR-15a/b accelerates fibrotic remodelling in the Type 2 diabetic human and mouse heart

Abstract: Myocardial fibrosis is a well-established cause of increased myocardial stiffness and subsequent diastolic dysfunction in the diabetic heart. The molecular regulators that drive the process of fibrotic events in the diabetic heart are still unknown. We determined the role of the microRNA (miR)-15 family in fibrotic remodelling of the diabetic heart. Right atrial appendage (RAA) and left ventricular (LV) biopsy tissues collected from diabetic and non-diabetic (ND) patients undergoing coronary artery bypass graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
56
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 41 publications
4
56
1
Order By: Relevance
“…Moreover, several other miRNAs that were in higher abundance in CMC db/db -derived EVs have been shown to have beneficial actions. For example, the levels of miR-15a, mi339–5p, and mi-370 were higher in EVs derived from CMC db/db cells, and these are thought to be involved in tissue regeneration or fibrosis [37, 51, 53]. That these in vitro measures of cell competence do not equate to in vivo efficacy is an important outcome of this study that merits further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, several other miRNAs that were in higher abundance in CMC db/db -derived EVs have been shown to have beneficial actions. For example, the levels of miR-15a, mi339–5p, and mi-370 were higher in EVs derived from CMC db/db cells, and these are thought to be involved in tissue regeneration or fibrosis [37, 51, 53]. That these in vitro measures of cell competence do not equate to in vivo efficacy is an important outcome of this study that merits further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Extensive atrial brosis resulting from hyperglycemia is thought to play a key role in both initiating and perpetuation AF as an increase of collagen deposition in the atria can cause abnormal conduction of signals, rupture of the propagating waves, and even the occurrence of re-entry 30 . In diabetic conditions, broblasts are activated leading to inappropriate collagen production and deposition no matter in type I DM 31,32 or type II DM [33][34][35] . Emerging evidence poses a unique challenge to understanding the pathogenesis of atrial brillation caused by diabetes, which is often consistent with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that miRs function as important regulators that participates in DM-induced atrial brosis 35 . The role of miR-21 in the pathogenesis of atrial brosis has been illuminated, and increased miR-21 expression was correlated positively with atrial brosis or brotic gene expression [20][21][22] signaling pathway by decrease CADM1 expression 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Extensive atrial fibrosis resulting from hyperglycemia is thought to play a key role in both initiating and perpetuation AF as an increase of collagen deposition in the atria can cause abnormal conduction of signals, rupture of the propagating waves, and even the occurrence of re-entry [30]. In diabetic conditions, fibroblasts are activated leading to inappropriate collagen production and deposition no matter in type I DM [31,32] or type II DM [33][34][35]. Emerging evidence poses a unique challenge to understanding the pathogenesis of atrial fibrillation caused by diabetes, which is often consistent with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that miRs function as important regulators that participates in DM-induced atrial fibrosis [35]. The role of miR-21 in the pathogenesis of atrial fibrosis has been illuminated, and [59,60].…”
Section: Discussionmentioning
confidence: 99%